Biomimetic 2D-Ni(Co, Fe)P/1D-WOx nanocoral reef electrocatalysts for efficient water splitting. Issue 17 (22nd April 2021) - Kim, Dokyoung; Jeong, Yongjae; Roh, Hyogyun; Lim, Chaeeun; Yong, Kijung
Abstract : Biomimetic nano coral reef (Ni(Co, Fe)P–WO x ) exhibits efficient water splitting electrocatalytic activity resulting from the excellent charge transport activity of WO x nanowire coral and superior HER and OER activity of Ni(Co, Fe)P nanosheet algae. Abstract : The design of efficient nanostructured electrocatalysts is highly desirable for promoting the hydrogen/oxygen evolution reactions (HER/OER), which are key processes of ecofriendly H2 production in water splitting systems. In this study, we present novel biomimetic hierarchical nanocoral reef materials as efficient and durable electrocatalysts for alkaline water splitting. Our nanocoral reef catalyst has a unique structure consisting of Ni(Co, Fe)P nanosheet (NS) algae and WO x nanowire (NW) corals. The WO x NW corals effectively transport charges (e − /h + ) to the Ni(Co, Fe)P NS algae through a 1D directional structure. The ultrathin 2D Ni(Co, Fe)P NS algae grown on the WO x NW corals provide an abundance of active sites for splitting water molecules into H2 and O2 . As a result, our hierarchical 2D-NS/1D-NW-structured NiCoP–WO x (HER) and NiFeP–WO x (OER) catalysts demonstrate excellent activities, requiring low overpotentials of 49 and 270 mV, respectively, to generate a current density of 10 mA cm −2 . Additionally, they exhibit high electrochemical stability for over 60 h in 1 M KOH. In addition, the overall water splitting (OWS) system, NiCoP–WO x (HER)‖NiFeP–WO x (OER) requires a cell voltage of 1.51 V to generate a current density of 10 mA cm −2 . This value is very low compared to other reported transition metal phosphides. The biomimetic engineering presented in the current study provides not only efficient electrocatalysts but also a promising, useful strategy to develop functional 1D/2D hierarchical materials for advanced energy applications.